Implementasi Metode Audio Lingual dalam Memperkuat Hafalan Materi Bahasa Arab di MTs Mathalibul Huda Mlonggo Jepara - Sajidah, Haniatul; Saefudin, Ahmad (Fakultas Tarbiyah dan Ilmu Keguruan, Universitas Islam Negeru Sultan Aji Muhammad Idris Samarinda, 2025)
The low interest of students in memorizing Arabic vocabulary has prompted educators to seek effective methods for the teaching and learning process. Vocabulary mastery is a crucial aspect of learning Arabic, as without it, students' abilities to understand, speak, read, and write in Arabic are severely limited. However, memorizing vocabulary is often perceived as a boring and difficult task, particularly when relying solely on traditional methods such as passively memorizing word lists. This study aims to examine the implementation of the Audio-Lingual Method at MTs Mathalibul Huda Mlonggo and assess its positive and negative impacts on students' memorization skills. A qualitative descriptive method was used, with data analysis conducted in three stages: data reduction, data presentation, and conclusion. The results indicate that the Audio-Lingual Method is effective in improving students' memorization of Arabic vocabulary, as it emphasizes repetition, listening and speaking exercises, and habituation through dialogue. Approximately 83% of students demonstrated mastery of the method, while 17% struggled to utilize it due to a lack of focus during the listening activities. Despite challenges such as differences in student abilities and limited resources, these obstacles can be overcome with teaching strategies and approaches tailored to students' characteristics. Therefore, the Audio-Lingual Method represents a relevant and effective alternative for enhancing students' Arabic vocabulary memorization and improving their overall language skills in a communicative and comprehensive manner.